Religious Moderation and Ecological Awareness in the Qur'an and Hadith Books of Muhammadiyah Senior Vocational High Schools - Maesaroh Maesaroh; Muqawwim (at-Tarbiyah al-Mustamirrah: Jurnal Pendidikan Islam, 2026)
This study examines religious moderation and ecological awareness in the Al-Qur’an and Hadith textbooks used in Muhammadiyah senior high schools and vocational schools, focusing on the representation of values, patterns of integration, and their pedagogical implications in Islamic education learning. The study aims to analyze the content of religious moderation and ecological awareness embedded in the textbooks and to explain their relevance to students’ character development. This research employed a qualitative approach using content analysis as the primary method. The main data sources consisted of Al-Qur’an and Hadith textbooks for Muhammadiyah SMA/SMK, which were analyzed through thematic identification, value categorization, meaning interpretation, and systematic conclusion drawing. The findings reveal that the textbooks contain values of religious moderation, including tolerance (tasamuh), balance (tawazun), justice (i‘tidal), and anti-extremism attitudes, which are presented through Qur’anic verses, hadiths, learning narratives, and reflective learning activities. In addition, the study found ecological awareness values reflected in the concept of humans as khalifah fil ardh, the prohibition of environmental destruction, and the responsibility to preserve ecological balance. The integration of these two dimensions demonstrates an orientation of Islamic education that emphasizes harmony between human relationships with God, fellow human beings, and the environment. Pedagogically, these findings imply the importance of contextual, humanistic, and religious-ecological character-based Islamic education learning. Keywords: Religious Moderation, Ecological Awareness, Al-Qur’an and Hadith textbooks, Islamic Education, Content Analysis.